Estimating downward shortwave radiation incorporating topographic effects using a hybrid physical and data-driven method: Algorithm development and long-term global product generation - Yichuan Ma; Tao He; Shunlin Liang; Xiaotong Zhang; Tim R. McVicar; Dejun Cai; Wanshan Peng; Yueming Zheng; Tong Liu; Xinyan Liu (Remote Sensing of Environment, 2026)

Accelerated charge transfer dynamics via a CoFe bimetallic oxide hole transport medium for enhanced photoelectrochemical water oxidation - Jiaxin Mao; Xingyu Zeng; Yuming Wu; Ziyan You; Wenfang Deng; Ming Ma; Yueming Tan (Chemical Engineering Journal, 2026)

In-situ constructed Ag/CNT hierarchical networks in TPU nanofibers for dual-mode triboelectric sensing - Shiqiang Ouyang; Feijie Wang; Yichi Liu; Suyang Wang; Yaoli Wang; Yuefan Liu; Zhixuan Mei; Kaixin Liao; Shenzhuo Zhang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Sealing behavior of bolted flange system with double metallic C-rings during prolonged high-temperature operation - Yijun Chai; Yunzhou Wu; Wenhao Yu; Qin Ma; Xiongwei Yang; Yueming Li (Annals of Nuclear Energy, 2026)

Engineering design paradigms for high-performance rotating triboelectric nanogenerators: From structural optimization to system synergy - Yan Ma; Feijie Wang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Analytical solution for transient groundwater flow to partially penetrated waterproof curtains in unconfined aquifers - Qian Wang; Jiangwei Zhang; Enze Ma; Yueming Qi; Liyang Xu; Yue Fan; Xiuyu Liang (Journal of Hydrology, 2026)

Insight into the pollution potential of different ecological types of lakes from the perspective of dissolved organic matter characteristics: Field and experimental evidence - Yang Deng; Longmian Wang; Yueming Zhu; Xiang Zhu; Qingqing Pang; Yuying Ma; Fuquan Peng; Lei Xie; Xiaoguang Xu; Qiu Jin; Guoxiang Wang; Fei Yang; et al. (Journal of Hydrology, 2025)

Analysis of temporal trends and spatial distributions in top-of-atmosphere shortwave radiation based on multiple datasets from satellites observations, reanalyses, and climate models - Yueming Zheng; Tao He; Yichuan Ma (Global and Planetary Change, 2025)

Montmorillonite-derived Mg-doped NaAlSiO4 for radiative cooling applications - Zhizheng Xiang; Zhongqiu Tong; Haowei Yang; Jie Yu; Yingjun Xiao; Yueming Wang; Shaoyuan Li; Xingang Li; Mikhail M. Mikhailov; Wenhui Ma (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Passive Synthetic Aperture for Direction-of-Arrival Estimation Using an Underwater Glider with a Single Hydrophone - Yueming Ma; Jie Sun; Shuo Li; Tianze Hu; Shilong Li; Yuexing Zhang (Journal of Marine Science and Engineering, 2025)
This paper addresses the aperture limitation problem faced by array-equipped underwater gliders (UGs) in direction-of-arrival (DOA) estimation. A passive synthetic aperture (PSA) method for DOA estimation using a single hydrophone mounted on a UG is proposed. This method uses the motion of the UG to synthesize a linear array whose elements are positioned to acquire the target signal, thereby increasing the array aperture. The dead-reckoning method is used to determine the underwater trajectory of the UG, and the UG’s trajectory was corrected by the UG motion parameters, from which the array shape was adjusted accordingly and the position of the array elements was corrected. Additionally, array distortion caused by movement offsets due to ocean currents underwent linearization, reducing computational complexity. To validate the proposed method, a sea trial was conducted in the South China Sea using the Haiyi 1000 UG equipped with a hydrophone, and its effectiveness was demonstrated through the processing of the collected data. The performance of DOA estimation prior to and following UG trajectory correction was compared to evaluate the impact of ocean currents on target DOA estimation accuracy.

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Mapping of Rsn2, a locus conferring rice tolerance to toxin from the causal agent of rice sheath blight Rhizoctonia solani - Xiang Xue; Yu Wang; Yueming Xu; Yumei Zhang; Fang Gu; Yuyin Ma; Zongxiang Chen; Yafang Zhang (Journal of Plant Pathology, 2025)

A Method for Multi-AUV Cooperative Area Search in Unknown Environment Based on Reinforcement Learning - Yueming Li; Mingquan Ma; Jian Cao; Guobin Luo; Depeng Wang; Weiqiang Chen (Journal of Marine Science and Engineering, 2024)
As an emerging direction of multi-agent collaborative control technology, multiple autonomous underwater vehicle (multi-AUV) cooperative area search technology has played an important role in civilian fields such as marine resource exploration and development, marine rescue, and marine scientific expeditions, as well as in military fields such as mine countermeasures and military underwater reconnaissance. At present, as we continue to explore the ocean, the environment in which AUVs perform search tasks is mostly unknown, with many uncertainties such as obstacles, which places high demands on the autonomous decision-making capabilities of AUVs. Moreover, considering the limited detection capability of a single AUV in underwater environments, while the area searched by the AUV is constantly expanding, a single AUV cannot obtain global state information in real time and can only make behavioral decisions based on local observation information, which adversely affects the coordination between AUVs and the search efficiency of multi-AUV systems. Therefore, in order to face increasingly challenging search tasks, we adopt multi-agent reinforcement learning (MARL) to study the problem of multi-AUV cooperative area search from the perspective of improving autonomous decision-making capabilities and collaboration between AUVs. First, we modeled the search task as a decentralized partial observation Markov decision process (Dec-POMDP) and established a search information map. Each AUV updates the information map based on sonar detection information and information fusion between AUVs, and makes real-time decisions based on this to better address the problem of insufficient observation information caused by the weak perception ability of AUVs in underwater environments. Secondly, we established a multi-AUV cooperative area search system (MACASS), which employs a search strategy based on multi-agent reinforcement learning. The system combines various AUVs into a unified entity using a distributed control approach. During the execution of search tasks, each AUV can make action decisions based on sonar detection information and information exchange among AUVs in the system, utilizing the MARL-based search strategy. As a result, AUVs possess enhanced autonomy in decision-making, enabling them to better handle challenges such as limited detection capabilities and insufficient observational information.

The unequal impacts of extremely high temperatures on households’ adaptive behaviors: Empirical evidence from fine-grained electricity consumption data - Han Shi; Bo Wang; Yueming Lucy Qiu; Nana Deng; Baichen Xie; Bin Zhang; Shijun Ma (Energy Policy, 2024)

Effects of Detritus Treatments on Soil Microbial Community Composition, Structure and Nutrient Limitation in a Subtropical Karst Ecosystem - Peiwen Liu; Suya Ding; Ning Liu; Yanhua Mo; Yueming Liang; Jiangming Ma (Journal of Soil Science and Plant Nutrition, 2024)

An Obstacle Avoidance Strategy for AUV Based on State-Tracking Collision Detection and Improved Artificial Potential Field - Yueming Li; Yuhao Ma; Jian Cao; Changyi Yin; Xiangyi Ma (Journal of Marine Science and Engineering, 2024)
This paper proposes a fusion algorithm based on state-tracking collision detection and the simulated annealing potential field (SCD-SAPF) to address the challenges of obstacle avoidance for autonomous underwater vehicles (AUVs) in dynamic environments. Navigating AUVs in complex underwater environments requires robust autonomous obstacle avoidance capabilities. The SCD-SAPF algorithm aims to accurately assess collision risks and efficiently plan avoidance trajectories. The algorithm introduces an SCD model for proactive collision risk assessment, predicting collision risks between AUVs and dynamic obstacles. Additionally, it proposes a simulated annealing (SA) algorithm to optimize trajectory planning in a simulated annealing potential field (SAPF), integrating the SCD model with the SAPF algorithm to guide AUVs in obstacle avoidance by generating optimal heading and velocity outputs. Extensive simulation experiments demonstrate the effectiveness and robustness of the algorithm in various dynamic scenarios, enabling the early avoidance of dynamic obstacles and outperforming traditional methods. This research provides an accurate collision risk assessment and efficient obstacle avoidance trajectory planning, offering an innovative approach to the field of underwater robotics and supporting the enhancement of AUV autonomy and reliability in practical applications.

Wide pH photocatalytic nitrate reduction at adaptive microenvironment-dominated liquid–liquid-solid trilayer reaction interfaces - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Chemical Engineering Journal, 2024)

Enhanced photocarrier separation in Br substitution-induced [W(VI)O6−x] units for highly efficient photocatalytic nitrate reduction under alkaline conditions - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Journal of Hazardous Materials, 2024)

A viologen-based conductive hydrogel enables iontophoresis devices powered by Mg biobattery - Yan Zhou; Shan Jiang; Xuenan Ma; Yueming Mu; Jiaxin Zhao; Qin Liang; Xiaoteng Jia; Danming Chao (Chemical Engineering Journal, 2023)

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Novel insights into Co synergy and electron-transfer pathways during the oxidation of contaminants by Cu-OOSO3- in CuCo2Ox/peroxymonosulfate system - Lele Zhao; Jiaming Zhang; Yuan Zong; Jun Ma; Chengying Bai; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2023)

High-ratio {100} plane-exposed ZnO nanosheets with dual-active centers for simultaneous photocatalytic Cr(VI) reduction and Cr(III) adsorption from water - Xiao Li; Jiajia Liu; Jing Feng; Tong Wei; Zhongxiang Zhou; Jun Ma; Yueming Ren; Yanqing Shen (Journal of Hazardous Materials, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

Integration of metabolomics and proteomics analysis to explore the mechanism of neurotoxicity induced by receipt of isoniazid and rifampicin in mice - Xiaoyu Qu; Jie Ma; Huan Gao; Yueming Zhang; Jinghui Zhai; Jiawei Gong; Yanqing Song; Tingting Hu (NeuroToxicology, 2023)

ZnS quantum dots implanted polyaniline-wrapped corn straw catalysts for efficient photocatalytic nitrate reduction without external addition of hole scavengers - Shuo Wang; Ying Zhao; Jing Feng; Tong Wei; Jun Ma; Yueming Ren; Chengying Bai (Chemical Engineering Journal, 2023)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Long-term forest restoration influences succession patterns of soil bacterial communities - Yueming Liang; Fujing Pan; Jiangming Ma; Zhangqi Yang; Peidong Yan (Environmental Science and Pollution Research, 2021)

Research on a novel extraction method using Deep Learning based on GF-2 images for aquaculture areas - Bo Cheng; Chenbin Liang; Xunan Liu; Yueming Liu; Xiaoxiao Ma; Guizhou Wang (International Journal of Remote Sensing, 2020)

Overexpression of d-psicose 3-epimerase from Ruminococcus sp. in Escherichia coli and its potential application in d-psicose production - Yueming Zhu; Yan Men; Wei Bai; Xiaobo Li; Lili Zhang; Yuanxia Sun; Yanhe Ma (Biotechnology Letters, 2012)

Phylogenetic relationship of a new class of LMW-GS genes in the M genome of Aegilops comosa - Ke Wang; Liyan Gao; Shunli Wang; Yanzhen Zhang; Xiaohui Li; Miaoyi Zhang; Zhenze Xie; Yueming Yan; Matthew Belgard; Wujun Ma (Theoretical and Applied Genetics, 2011)

Gene networks in the synthesis and deposition of protein polymers during grain development of wheat - Maoyun She; Xingguo Ye; Yueming Yan; C. Howit; M. Belgard; Wujun Ma (Functional & Integrative Genomics, 2011)

Molecular characterization of the celiac disease epitope domains in α-gliadin genes in Aegilops tauschii and hexaploid wheats (Triticum aestivum L.) - Zhenze Xie; Congyan Wang; Ke Wang; Shunli Wang; Xiaohui Li; Zhao Zhang; Wujun Ma; Yueming Yan (Theoretical and Applied Genetics, 2010)

Cloning and characterization of a novel low molecular weight glutenin subunit gene at the Glu-A3 locus from wild emmer wheat (Triticum turgidum L. var. dicoccoides) - Xiaohui Li; Aili Wang; Yinghua Xiao; Yueming Yan; Zhonghu He; Rudi Appels; Wujun Ma; S. L. K. Hsam; F. J. Zeller (Euphytica, 2008)

Berechnung von Temperatur- und Spannungszuständen in RCC-Staumauern - Yueming Zhu; Stephan Semprich; Yuefeng Ma; Weimin Cao; Hong Wang (WASSERWIRTSCHAFT, 2007)